2009
DOI: 10.1103/physrevlett.102.135002
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Dark Soliton in a Complex Plasma

Abstract: The observation of a dark soliton in a three-dimensional complex plasma containing monodisperse microparticles is presented. We perform our experiments using neon gas in the bulk plasma of an rf discharge. A gas temperature gradient of 500K/m is applied to balance gravity and to levitate the particles in the bulk plasma. The wave is excited by a short voltage pulse on the electrodes of the radio frequency discharge chamber. It is found that the wave propagates with constant speed. The propagation time of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 32 publications
3
66
0
1
Order By: Relevance
“…Nowadays, there is a great deal of interest in nonlinear DA waves because of their vital role in understanding the properties of the localized electrostatic perturbations in space and laboratory dusty plasmas [14]- [20]. The nonlinear DA waves have been investigated theoretically [1], [21]- [27], as well as experimentally [28]- [35] over the last few years. However, most of these theoretical works [1], [21]- [27] are limited to a weakly coupled dusty plasma, where the coupling parameter (= 0 exp(−κ), in which 0 = z 2 average inter-grain distance, T d is the dust temperature in units of the Boltzmann constant, λ D is the dusty plasma Debye radius, and n d0 is the equilibrium dust number density) is much less than one ( 1).…”
mentioning
confidence: 99%
“…Nowadays, there is a great deal of interest in nonlinear DA waves because of their vital role in understanding the properties of the localized electrostatic perturbations in space and laboratory dusty plasmas [14]- [20]. The nonlinear DA waves have been investigated theoretically [1], [21]- [27], as well as experimentally [28]- [35] over the last few years. However, most of these theoretical works [1], [21]- [27] are limited to a weakly coupled dusty plasma, where the coupling parameter (= 0 exp(−κ), in which 0 = z 2 average inter-grain distance, T d is the dust temperature in units of the Boltzmann constant, λ D is the dusty plasma Debye radius, and n d0 is the equilibrium dust number density) is much less than one ( 1).…”
mentioning
confidence: 99%
“…This concurrence leads to the formation of some effective electric field inside the moving narrow dust cloud that confines dust particles, prevents them from dispersing, and decreases the damping of the cloud velocity. It should be mentioned that there have been several experimental studies on the propagation of nonlinear dust acoustic solitary waves [16,17], which showed an unexpectedly low damping rate of soliton velocity.…”
Section: Methodsmentioning
confidence: 98%
“…[41][42][43][44][45]. So far, the dissipative bright solitons have been extensively investigated and dissipative dark soliton in plasma was also discussed in [46], while the formation of dissipative dark solitons in fiber lasers has not been addressed. In this paper, based on the operation of an all-normal dispersion fiber laser that has a typical NPR mode locking cavity configuration, we numerically show that depending on the setting of the linear cavity phase delay bias (LCPDB), the same laser could operate in different modes: either in CW emission, or dark soliton emission, or bright soliton emission.…”
Section: Introductionmentioning
confidence: 98%